Corrigendum to “Analysis of domain shift in whole prostate gland, zonal and lesions segmentation and detection, using multicentric retrospective data” [Comput. Biol. Med. 17 (2024) 108216] - ProCAncer-I Consortium (2024)
ProCAncer-I Consortium, Rodrigues, N. M., de Almeida, J. G., Castro Verde, A. S., Gaivão, A. M., Bilreiro, C., Santiago, I., Ip, J., Belião, S., Moreno, R., Matos, C., Vanneschi, L., Tsiknakis, M., Marias, K., Regge, D., Silva, S., & Papanikolaou, N. (2024). Corrigendum to “Analysis of domain shift in whole prostate gland, zonal and lesions segmentation and detection, using multicentric retrospective data” [Comput. Biol. Med. 17 (2024) 108216]. Computers in Biology and Medicine, 1. Article 108352. https://doi.org/10.1016/j.compbiomed.2024.108352